Pengembangan Media Pembelajaran Interaktif Menggunakan Google Sites Pemeliharaan Chasis Sepeda Motor Program Keahlian TBSM Kelas XI SMK Muhammadiyah Berbah - Muhammad Egi Ebriasdi; Samidjo; setuju (JURNAL VOKASI DEWANTARA (JVD), 2025)
Muhammad Egi Ebriasdi. 2020006024. Development of Interactive Learning Media Using Google SitesMotorcycle Chassis Maintenance TBSM Expertise Program for Class XI SMK Muhammadiyah Berbah.Thesis Vocational Education Study Program in Mechanical Engineering, Faculty of Teacher Training andEducation, Sarjanawiyata University, Tamansiswa 2024. This study aims to 1) Produce interactivelearning media products using Google Sites on Motorcycle Chassis Maintenance material; 2) Determinethe feasibility of interactive learning media using Google Sites in Motorcycle Chassis Maintenancelearning; 3) Determine the response of class XI Motorcycle Engineering and Business students at SMKMuhammadiyah Berbah after using Google Sites learning media. This research and development uses the4-D (Four-D) model, which consists of the Define, Design, Development, Disseminate stages. Theresearch subjects consisted of media experts, material experts, and class XI Motorcycle Engineering andBusiness (TBSM) students at SMK Muhammadiyah Berbah. The instrument used was a questionnaire.The data analysis technique used descriptive percentage analysis. The results of the study showed that: 1)This study produced interactive learning in the form of a Motorcycle Chassis Maintenance subject modulefor class XI TBSM based on a website that is accessed via a link on Google Sites; 2) The feasibility oflearning media using Google Sites on the Motorcycle Chassis Maintenance subject is very feasible to usewith the results of the validation test by media experts with a score of 81% and the results of the validationtest by material experts 76%; 3) The average student stated a happy response to be used during learningwith a small-scale test score of 83% and a large-scale test getting a score of 82%.